Valgus malalignment is a risk factor for lateral knee osteoarthritis incidence and progression: Findings from the multicenter osteoarthritis study and the osteoarthritis initiative - Felson, David T.; Niu, Jingbo; Gross, K. Douglas; Englund, Martin; Sharma, Leena; Cooke, T. Derek V.; Guermazi, Ali; Roemer, Frank W.; Segal, Neil; Goggins, Joyce M.; Lewis, C. Elizabeth; Eaton, Charles; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2013)
Objective To study the effect of valgus malalignment on knee osteoarthritis (OA) incidence and progression. Methods We measured the mechanical axis from long limb radiographs from the Multicenter Osteoarthritis Study (MOST) and the Osteoarthritis Initiative (OAI) to define limbs with valgus malalignment (mechanical axis of ≥1.1° valgus) and examined the effect of valgus alignment versus neutral alignment (neither varus nor valgus) on OA structural outcomes. Posteroanterior radiographs and knee magnetic resonance (MR) images were obtained at the time of the long limb radiograph and at followup examinations. Lateral progression was defined as an increase in joint space narrowing (on a semiquantitative scale) in knees with OA, and incidence was defined as new lateral narrowing in knees without radiographic OA. We defined lateral cartilage damage and progressive meniscal damage as increases in cartilage or meniscus scores at followup on the Whole‐Organ Magnetic Resonance Imaging Score scale (for the MOST) or the Boston Leeds Osteoarthritis Knee Score scale (for the OAI). We used logistic regression with adjustment for age, sex, body mass index, and Kellgren/Lawrence grade, as well as generalized estimating equations, to evaluate the effect of valgus alignment versus neutral alignment on disease outcomes. We calculated odds ratios (ORs) and 95% confidence intervals (95% CIs). Results We studied 5,053 knees (881 valgus) of subjects in the MOST cohort and 5,953 knees (1,358 valgus) of subjects in the OAI cohort. In both studies, all strata of valgus malalignment, including 1.1° to 3° valgus, were associated with an increased risk of lateral disease progression. In knees without radiographic OA, valgus alignment >3° was associated with incidence (e.g., in the MOST, adjusted OR 2.5 [95% CI 1.0–5.9]). Valgus alignment >3° was also associated with cartilage damage on MR imaging in knees without OA (e.g., in the OAI, adjusted OR 5.9 [95% CI 1.1–30.3]).We found a strong relationship of valgus malalignment with progressive lateral meniscal damage. Conclusion Valgus malalignment increases the risk of knee OA radiographic progression and incidence as well as the risk of lateral cartilage damage. It may cause these effects, in part, by increasing the risk of meniscal damage.